Walking the city : the geographies of everyday pedestrian practices - Middleton, J (Wiley, 2011)
Concerns with walking cut across both policy and academic arenas, ranging from its promotion as a significant mode of sustainable transport to it being drawn upon as an artistic practice. However, there remains a disconnection between different bodies of research addressing different dimensions associated with walking, whereby a distinction can be drawn between understanding walking as a topic and subject to research and drawing upon walking as a method of enquiry. This paper aims to critically explore some of the multiple areas of work on walking and in so doing proposes an increased dialogue between and wider acknowledgement of, different modes of enquiry relating to pedestrian practices. More specifically the paper explores policy concerns with pedestrian movement; how walking is situated within writings concerning the democratic possibilities of urban public space; its role in performative engagements with the city; pedestrian movement as a means of reading/knowing urban space; and the relationship between walking and art. In so doing, the potential is explored for how these forms of engagement with walking translate into, or provide a medium for, the broader concerns of those such as policymakers as to who walks and why.